Kristeva as Semiotician Today - Bennett, Tyler James (Acta Nova Humanistica: A Journal of Humanities Published by New Bulgarian University, 2024)
Even a cursory exploration of the international semiotics scene today reveals that the work of Julia Kristeva is underrepresented. The radical- ism of her texts is an abiding reason for the fact that Semeiotike remains stubbornly "inconvertible" (Nikolchina 2011) into mainstream semiotics. This essay elaborates two opposed philosophical temperaments and a series of functional dualisms, including signification vs. communication and quasi-sign vs. fully fledged sign, in connection with Kristeva's own dualism, the symbolic vs. the semiotic. The quasi-sign doctrine is just one example of how Kristevan dualisms make possible non-reductive existential and social commitments and afford a written textual method applicable across the board in general semiotics. The Kristevan methods of polylogue, narrativization, and auto-critique are highest-order humanities tools for regulating ideology at the level of the text; they also contribute to the inconvertibility of Kristeva's books as hermetic and seemingly incomprehensible artifacts. The interest of these methods is intractable to quantitative methods and non-describable by natural science. This is one reason we provide such an effective interdisciplinary framework in humanities research - as semiotics aligns more and more with the strug- gle to revitalize the problematic humanities, Kristeva remains/returns as a core theoretic coordinate.